PENGARUH RISIKO BISNIS, KEBIJAKAN DIVIDEN DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDOENSIA TAHUN 2013 – 2015) - Ramaiyanti, Sinta; Nur, Emrinaldi; Basri, Yesi Mutia (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
This study aims to determine the effect of business risk, dividend policy and firmsize partially to financial performance. Furthermore, this study also examines the role of capital structure as the mediation of the relationship between business risk, dividend policy and firm size with financial performance. Population in this research is a manufacturing company listed on Indonesia Stock Exchange (IDX) between the years 2013 to 2015 has been used.. The sampling method used in this study is purposive sampling, so that obtained 71 samples. This study uses secondary data obtained from the website of Indonesia Stock Exchange and Bank Indonesia. The statistical method used to test the research hypothesis is the Structural Equation Model (SEM) based on Partial Least Square (PLS) with the help of the WarpPLS 6.0 program.The result of this research proves that business risk, dividend policy has a negative and significant effect on capital structure, while firm size has a positive and significant effect on capital structure. Then the capital structure has a negative and significant effect on financial performance.Business risk has positive and significant effect to financial performance whille dividend policy and firm size has no effect to financial performance. Furthermore, business risk, dividend policy, and firm size partially affect the financial performance through the capital structure.